PENGARUH METODE SCHOOL WATCHING TERHADAP KESIAPSIAGAAN SISWA SD DALAM MENGHADAPI BENCANA DI KECAMATAN CICENDO KOTA BANDUNG - Lia Meilianingsih; Sugiyanto Sugiyanto (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2022)
West Java Province has the highest level of disaster vulnerability in Indonesia, which is dominated by landslides, floods and fires. The group that is most vulnerable to disasters is children. Elementary school student spends an average of 7 hours in school. So, the school can be categorized as a disaster-prone place. Disasters can occur at any time, including when students are in school. School children must have resilience in facing the threat of disaster. School Watching is one method that can assist students in improving disaster preparedness through activities carried out in schools and the surrounding environment. This study aims to determine the effect of the school watching method on the preparedness of elementary school students in dealing with disasters in Cicendo District, Bandung City. The research design used a quasi-experimental approach with a Pre-Post test control group design approach. The sample of this study was fifth grade elementary school students in Cicendo District. The sample size is 39 people for the intervention group and 39 people for the control group. The sampling technique is proportional random sampling. The intervention was given in 5 meetings. Intervention activities include: providing materials on disaster, observations, mapping, discussions and presentations. Analysis of the data used for the paired group using a statistical test T test dependent because the data is normally distributed. Meanwhile, for the unpaired group, the Mann-Whitney test was used because the data were not normally distributed. The results showed that there was an effect of the school watching method on the preparedness of elementary school students in dealing with disasters because the p value was 0.000. Therefore, it is suggested to the person in charge of the school health program to apply the school watching method to reduce disaster risk in the school community.